Monitoring the Assessment of Vernacular Buildings using an ICT Method - Virtudes, Ana L. (2020)
Nowadays, one of the main challenges in high levels of education, is to deal with ICT as a tool in teaching methodologies. This article aims to present some results of the use of an ICT platform as a tool in spatial analysis. It is focused on the study of vernacular architecture buildings, based on the case study of wooden house villages of Tagus river banks, in Portugal. This is the unique legacy in this country, of wooden vernacular architecture in areas submitted to regular floods. The main typology of these buildings refers to stilt-houses, which have their roots in the middle XIX century. Along the time, they have been subjected to a degradation process caused by the lack of repair actions, driving to an aggravation of their status of conservation, or caused by repair actions, driving to an aggravation of their distance to the vernacular architectural matrix. Consequently, there are less than one hundred buildings remaining in five villages. The used ICT tool refers to the software DECMAvi, which is an evaluation method of buildings, designed on purposes to analyse two criteria of these territories of vernacular architecture; the status of buildings conservation and their level of proximity to the vernacular architectural matrix. This method was tested firstly in 2014 and then in 2016, and the results are allowing to obtain results coming from a comparative analysis during this period of time, in order to know if the buildings are better, worst or in same condition, and from a spatial analysis in between the considered villages and their vernacular buildings.